Towards a Sociology of Ecuadorian Sociology - Altmann , Philipp (2022)
Ecuadorian sociology is defined by its radical ruptures. On several occasions, personal, institutional, political and epistemological changes led to a new beginning and a tabula rasa attitude. With that, it was impossible to discuss and overcome the previous phases. This text argues that there are also continuities that would be worth exploring to enrich the current sociological debate. The continuities are presented in a set of themes that defined Ecuadorian sociology from the beginning and that continue to be important today. Themes are understood in Nisbet's sense as unit-ideas, that is, basic ideas that define fields of debate. These themes are: the indigenous population and rural sociology, democracy and populism, inequality and social classes, Marxism.